Binding of a Telomestatin Derivative Changes the Mechanical Anisotropy of a Human Telomeric G‐Quadruplex. Issue 3 (12th December 2018) - Jonchhe, Sagun; Ghimire, Chiran; Cui, Yunxi; Sasaki, Shogo; McCool, Mason; Park, Soyoung; Iida, Keisuke; Nagasawa, Kazuo; Sugiyama, Hiroshi; Mao, Hanbin
Abstract: Mechanical anisotropy is an essential property for biomolecules to assume structural and functional roles in mechanobiology. However, there is insufficient information on the mechanical anisotropy of ligand–biomolecule complexes. Herein, we investigated the mechanical property of individual human telomeric G‐quadruplexes bound to telomestatin, using optical tweezers. Stacking of the ligand to the G‐tetrad planes changes the conformation of the G‐quadruplex, which resembles a balloon squeezed in certain directions. Such a squeezed balloon effect strengthens the G‐tetrad planes, but dislocates and weakens the loops in the G‐quadruplex upon ligand binding. These dynamic interactions indicate that the binding between the ligand and G‐quadruplex follows the induced‐fit model. We anticipate that the altered mechanical anisotropy of the ligand–G‐quadruplex complex can add additional level of regulations on the motor enzymes that process DNA or RNA molecules. Abstract : 99 red balloons : Binding of a telomestatin analogue strengthens the mechanical stability of G‐tetrads, while weakening that of loops in a human telomeric G‐quadruplex. The mechanical anisotropy effect is sustained by the uneven structural variation of the G‐quadruplex after ligand binding, similar to a balloon squeezed in certain directions (the squeezed balloon effect).